Determinants of Bank Selection Choices in Malaysia: A Demographic based Investigation - Celestine Fernandez, Dominic (2008)
Banking is an important contributor to the economic growth around the world. The benefits of understanding consumer selection decisions will provide bankers with a competitive advantage as it has the ability to influence the marketing mix. With rising overheads and price competition, the profit margins earned from bank services are being narrowed. Banks will have to capture a sizeable customer base to sustain their profitability and turnover. Malaysia was chosen for this study as banks have been consolidating in recent times and the diversity of ethnicity, culture and demographic factors prevalent in this country would certainly have an impact of the bank selection behaviour in Malaysia. To accomplish this purpose, data for this study was obtained via a survey. The survey results indicated no attribute obtained was an outright determinant of bank selection choices. This was attributed to the diverse needs of respondents as revealed by this survey. While some determinants such as location was of prime importance when selecting a bank, other factors that emphasize of better social interaction between banker and client, is gaining prominence partly due to the influence of Asian culture. It also revealed the use of the consumer decision making model when selecting bank choices. As a whole, this study was able to achieve its objective in understanding and providing a snapshot of the important determinants in bank selection based on the feedback from survey respondents. How a larger sample over a greater length of time is deemed to provide a better understanding of trends in Malaysia.